Visualizing Phylogenetic Trees: Algorithms And Visual Comparison Techniques - Wan Zainon, Wan Mohd Nazmee (2011)
This thesis is about visualizing tree structured data. In particular, the emphasis is on visualizing the similarities and differences between pairs of trees. There are many research areas (such as biology, linguistics, chemistry and computer science) that use the tree as a basic data structure. The impetus for the work comes from the field of bioinformatics, where biologists construct complex phylogenetic trees to represent the evolution of species or genes. Once phylogenetic trees reveal potential interrelationships between examined species, the next step would be to validate the derived data.